Pengaruh Manajemen Laba Terhadap Fraud dengan Good Corporate Governance sebagai Variabel Moderasi - Syifa Mahira Amalia Putri; Purnomo, Budi S.; Supriatna, Nono (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This research was conducted based on the phenomenon of unethical behavior carried out by management, which resulted in low public trust. The aim of this research is to determine the influence of earnings management on fraud, and to determine the role of good corporate governance in moderating the influence of earnings management on fraud. This research uses a quantitative approach with an explanatory method on secondary data in the form of company annual reports, with a total sample of 135. Hypothesis testing uses SPSS as the analysis tool. The results show that earnings management significantly and positively influences fraud, while good corporate governance has a significant negative influence on fraud. However, good corporate governance is not proven to moderate the relationship between earnings management and fraud. These results indicate the importance of stronger internal control and the optimal role of the audit committee to prevent fraud in earnings management practices.